Temporal logic model of performance in high school = Темпорально-логическая модель деятельности обучаемого в вузе - Pavlenko, V. N.; Tkachenko, Y. M. (Journal of Education, Health and Sport, 2015)
Pavlenko V. N., Tkachenko Y. M. Temporal logic model of performance in high school = Темпорально-логическая модель деятельности обучаемого в вузе. Journal of Education, Health and Sport. 2015;5(7):258-270. ISSN 2391-8306. DOI 10.5281/zenodo.19970 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A258-270 https://pbn.nauka.gov.pl/works/584328 http://dx.doi.org/10.5281/zenodo.19970 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2015. Revised 05.07.2015. Accepted: 12.07.2015. TEMPORAL LOGIC MODEL OF PERFORMANCE IN HIGH SCHOOL ТЕМПОРАЛЬНО-ЛОГИЧЕСКАЯ МОДЕЛЬ ДЕЯТЕЛЬНОСТИ ОБУЧАЕМОГО В ВУЗЕ V. N. Pavlenko, Y. M. Tkachenko В. Н. Павленко, Ю. М. Ткаченко National Aerospace University «Kharkiv Aviation Institute», Ukraine Национальный аэрокосмический университет им. Н. Е. Жуковского «ХАИ», Украина V.N. Pavlenko, NationalAerospaceUniversity«Kharkiv Aviation Institute», Ukraine Chkalova str. 17,Kharkiv,Ukraine, 61070 E-mail: pavlenko_vitaliy@mail.ru Y.M. Tkachenko, NationalAerospaceUniversity«Kharkiv Aviation Institute», Ukraine Chkalova str. 17,Kharkiv,Ukraine, 61070 E-mail: juli.tkachenko@mail.ru Abstract: The one of the stages of the approach to the organization of computer decision support to determine the trajectory of training of students in universities, namely the synthesis of model student. For the synthesis of the student model used mathematical apparatus of temporal logic. The form of a software implementation, the student model is representation in the form of an intelligent agent. Further stages of developing a new approach based on the development of the model of the student group as a community of intelligent agents, and on the notion of the learning process of students in the form of multi-agent system. A multi-agent system will be used to support decision-making by different levels (deans, vice-rector for scientific and pedagogical work) in the event of disputes in the learning process of individual students and student groups. Keywords: student, student group, the trajectory of education, educational process, process model, multi-agent systems, intelligent agents, temporal logic. Аннотация: изложен один из этапов реализации подхода к организации компьютерной поддержки принятия решений по определению траектории обучения студентов в ВУЗах, а именно синтез модели обучаемого. Для синтеза модели обучаемого использован математический аппарат темпоральной логики. Формой программной реализации модели обучаемого является его представление в виде интеллектуального агента. Дальнейшие этапы разрабатываемого подхода основаны на разработке модели студенческой группы как сообщества интеллектуальных агентов, и на представлении процесса обучения студентов в форме мультиагентной системы. Мультиагентная система будет использоваться для поддержки принятия решений руководителями разных уровней (деканами, проректорами по научно-педагогической работе) при возникновении спорных ситуаций в процессе обучения как отдельных студентов, так и студенческих групп. Ключевые слова: студент, студенческая группа, траектория обучения, образовательный процесс, процессная модель, мультиагентные системы, интеллектуальные агенты, темпоральная логика.